SmartIrrigation Avocado App: A Step-by-Step Guide - D. Mbabazi; Kati W. Migliaccio; Jonathan H. Crane; J.H. Debastiani Andreis; Clyde Fraisse; Lincoln Zotarelli; Kelly T. Morgan (EDIS, 2015)
UF’s SmartIrrigation Avocado for iOS and Android platforms provides a simple ET-based method to schedule irrigation and is expected to provide 20% to 50% water savings based on findings with other schedule tools. This 6-page fact sheet provides configuration instructions and main menu features. Written by D. Mbabazi, K. W. Migliaccio, J. H. Crane, J. H. Debastiani Andreis, C. Fraisse, L. Zotarelli, and K. T. Morgan, and published by the UF Department of Agricultural and Biological Engineering, May 2015.